Effect of Pruning Severity on Yield, Drying Time and Wages in Flame Seedless Dry-on-vine and Traditional Raisin Production Systems in Argentina - Espíndola, R.S.; Camargo, J.A.; Pringles, E.; Battistella, M. (South African Journal of Enology and Viticulture, 2018)
Raisin grapes are potentially more profitable than wine grapes in San Juan, Argentina, although the traditional system of grape drying requires an extensive use of costly labour. Production costs might be reduced by adopting the dry-on-vine (DOV) raisin-making system, but the feasibility of DOV in Argentina has not been assessed, and neither have the costs and pruning schemes. Thus we determined drying time and yields, estimated wages per hectare, and determined the influence of pruning severity on Flame Seedless raisin grapes. A completely random design with six treatments and six replicates was used in the 2013 to 2016 seasons. The treatments comprised differences in the nodes per cane, nodes per vine, distribution of nodes, and sugar content. Descriptive statistics and variance analysis were calculated for fresh fruit weight, dry fruit weight, drying ratio and drying time. The leaf area and its relationship with dried fruit weight also were calculated. These data were processed with the Infostat program. The DOV system demands between 11 and 31 additional days during the drying period and reduces labour costs by between 38% and 64% compared to the traditional system. Long pruning with the same load of buds is better. Furthermore, the DOV system is not associated with a lower production and thus appears to be a financially sustainable alternative to traditional production systems for Flame Seedless raisin grape producers in Argentina.